O sentido da educação superior no Curso de Pedagogia no Campus de Arraias/TO - Cunha, Suiane Reges da (Universidade Federal do Tocantins, 2020)
The presence of the university in a given region significantly contributes to diversifying access to knowledge. Consequently, the scientific bias of this research is guided by analyzing the importance of the Pedagogy Course at the Federal University do Tocantins - Campus Arraias, both for incoming students and for students those who are finishing the educational course at the higher level. In addition, this The article also aims to analyze the students' training process through higher education and there is also a proposal to understand how higher education training for students in the referred institution, which serves subjects from the Southeast of Tocantins and Northeast of the State Goiás, has collaborated with the regional population that is in a context full of inequalities. For this, this work was elaborated from the experiences acquired during the along the training acquired in the Full Degree Course in Pedagogy, consisting of through the nature of qualitative research, where questionnaires and reports of experiences involving students in the initial and final stages of the Pedagogy Course in 2019. With regard to the theoretical foundation of the work, it had as main theoretical support the contribution of authors such as Berbel (2011), Cambi (1999), Elias (1994) Freire (1989) Romanelli (1991) and Valadão (2018).